2000
DOI: 10.1038/35019000
|View full text |Cite
|
Sign up to set email alerts
|

Fringe is a glycosyltransferase that modifies Notch

Abstract: Notch receptors function in highly conserved intercellular signalling pathways that direct cell-fate decisions, proliferation and apoptosis in metazoans. Fringe proteins can positively and negatively modulate the ability of Notch ligands to activate the Notch receptor. Here we establish the biochemical mechanism of Fringe action. Drosophila and mammalian Fringe proteins possess a fucose-specific beta1,3 N-acetylglucosaminyltransferase activity that initiates elongation of O-linked fucose residues attached to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
688
0
7

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 801 publications
(706 citation statements)
references
References 47 publications
11
688
0
7
Order By: Relevance
“…LFNG encodes a glycosyltransferase that post-translationally modifies the Notch family of cell surface receptors, a key step in the regulation of this signaling pathway (Haines and Irvine, 2003). The LFNG protein is a fucose-specific ␤-1,3-N-acetylglucosaminyltransferase (Bruckner et al, 2000;Moloney et al, 2000) that functions in the Golgi to post-translationally modify the Notch receptors, altering their signaling properties (Haines and Irvine, 2003). Earlier studies have shown that Lfng gene expression is severely disregulated in Dll3-null mice, suggesting that Lfng expression is dependent on Dll3 function Kusumi et al, 2004).…”
Section: Lunatic Fringementioning
confidence: 99%
“…LFNG encodes a glycosyltransferase that post-translationally modifies the Notch family of cell surface receptors, a key step in the regulation of this signaling pathway (Haines and Irvine, 2003). The LFNG protein is a fucose-specific ␤-1,3-N-acetylglucosaminyltransferase (Bruckner et al, 2000;Moloney et al, 2000) that functions in the Golgi to post-translationally modify the Notch receptors, altering their signaling properties (Haines and Irvine, 2003). Earlier studies have shown that Lfng gene expression is severely disregulated in Dll3-null mice, suggesting that Lfng expression is dependent on Dll3 function Kusumi et al, 2004).…”
Section: Lunatic Fringementioning
confidence: 99%
“…1A for details, Wu et al, 1996;Johnston et al, 1997;Cohen et al, 1997;Laufer et al, 1997;Rodriguez-Esteban et al, 1997;Cadinouche et al, 1999;Mikami et al, 2001), including a putative signal peptide, potential N-linked glycosylation sites, a DXDmotif responsible for the glycosyltransferase catalytic activity (Moloney et al, 2000;Brü ckner et al, 2000) and six conserved cysteines that are thought to form disulfide bonds (Irvine and Wieschaus, 1994). Interestingly, the putative tetrabasic proteolytic sites are only found in Xenopus and chicken Rfng, suggesting that zebrafish, newt, rat, mouse, and human Rfng proteins may not require regulated proteolytic activation.…”
Section: Cloning and Sequence Analysismentioning
confidence: 99%
“…One of its major roles consists in the specification of border cells at boundaries between juxtaposed cell populations (reviewed in Irvine and Rauskolb, 2001). This process depends on Fringe, a glycosyltransferase (Moloney et al, 2000;Brü ckner et al, 2000) that can glycosylate Notch. This process is thought (in Drosophila at least) to make Notch more susceptible to activation by its ligand Delta and less susceptible to activation by the alternative ligand Serrate.…”
Section: Introductionmentioning
confidence: 99%
“…These structures vary significantly between cell types and at different stages of mammalian development and probably play important roles in the interaction of a cell with its cellular and fluid environment (3)(4)(5). Glycoproteins and proteoglycans are essential for normal development in mice (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), Drosophila melanogaster (17)(18)(19)(20), and Caenorhabditis elegans (18,(21)(22)(23)(24)(25)(26). Table 1 lists mice with null mutations in genes required for glycosylation; other null mutant mice are described in reviews by Stanley (9) and Varki and Marth (11).…”
mentioning
confidence: 99%